Body composition in children with chronic inflammatory diseases: A systematic review. Issue 9 (September 2020) - Houttu, Noora; Kalliomäki, Marko; Grönlund, Minna-Maija; Niinikoski, Harri; Nermes, Merja; Laitinen, Kirsi
Summary: Background & aims: Aberrations in body composition are expected in children suffering from chronic inflammatory conditions. The objective is to examine whether children with inflammatory bowel disease (IBD: Crohn's disease and ulcerative colitis), coeliac disease, asthma and juvenile idiopathic arthritis (JIA) have an altered body composition as compared to healthy children. Methods: A systematic review, registered in Prospero (registration number: CRD42018107645), was conducted according to PRISMA guidelines. We conducted a search of three databases, Pubmed, Cochrane and Scopus. An assessment of the quality of the study was performed. Results: Data from 50 studies, 32 with IBD, 8 with coeliac disease, 2 with asthma and 8 with JIA, involving 2399 children were selected for review after applying the eligibility criteria. In all but 4 studies, children with Crohn's disease exhibited decreased amounts of fat mass and fat free mass. Reductions in fat mass were also evident in studies in children with coeliac disease. It is uncertain whether body composition is altered in children with asthma or JIA. Conclusions: Children with Crohn's disease manifest with lowered adiposity and lean mass and therefore are likely to be at risk for suffering malnutrition-related clinical complications. Apart from Crohn's disease, data examining body composition in children with chronic inflammatory conditions are scarce and there is a paucity of reports examining the relationship between inflammation and body composition. Interpretation of the current study results is hampered by the low quality of the studies and due to the fact that the analyses have been habitually secondary outcomes. Highlights: Body composition analysis may help nutritional assessment in chronic diseases. A range of factors contribute to body composition changes in chronically ill. A little data exists on body composition in children with inflammatory conditions. Children with Crohn's disease manifest with lowered adiposity and lean mass.